In the question of the relationship between religion and art in the philosophy of Frederic Nietzsche. - boudejnane, mohamed el amin; afiane, mohamed (Journal of Social Sciences and Humanities, 2023)
In this study, we try to approach a controversial issue in contemporary Western philosophical and cultural circles about human destiny after scientific reasoning and theological values and their tendency towards abstract reason, and then look for the possibility of replacing metaphysical ethics with artistic and aesthetic values. We chose to address these problems due to two basic considerations: the emergence of new challenges to man after the domination of ideological institutions, theological values, and philosophical systems that relied on the mind and its satires, and thus proclaimed the birth of supernatural creation and rigid thought, in which mechanical, instrumental reason prevailed at the expense of sense, the dynamic aesthetic sense, as for the second reason; He traces Nietzsche's philosophy as an important turning point in the history of philosophical discourse, as it exposed the contradictions hidden behind philosophical consciousness, and reconstructed a strategy of interpretation and reflection. Using the analytic approach of Nietzsche's texts on Christian theology and art, and for the methodological and epistemological necessity, we applied the critical approach by undermining some common perceptions of moral and aesthetic values. And one of our findings is that there is a great conflict between what artistic values seek and what Christian values promote. If Christian morality seeks to kill man's will to be meadow, submissive and filled with hatred towards life, art creates the transcendent man of Christian pessimism.